Homo absconditus - Krüger, Hans-Peter (Walter de Gruyter GmbH, 2020)
This volume examines the specifics of Plessner's philosophy in comparison with the conceptions of Dewey, Freud, Habermas, Heidegger, Jaspers, Kant, Nietzsche, v. Uexküll and today's brain, cognition and behavioral research. It shows how philosophical anthropology overcomes the speciesism, ethnocentrism, anthropocentrism of modernity in favour of a common and open future of personal life forms.